RSV prophylaxis use in high-risk infants in Western Australia, 2002-2013: a record linkage cohort study - Ruomei Xu; Parveen Fathima; Tobias Strunk; Nicholas de Klerk; Thomas L. Snelling; Peter C. Richmond; Anthony D. Keil; Hannah C. Moore (BMC, 2020)
Abstract Background The monoclonal antibody, palivizumab is licensed for use in high-risk infants to prevent severe illness caused by respiratory syncytial virus (RSV). The level of its use and compliance with current jurisdictional guidelines which were amended in 2010, is unknown. We determined the level of palivizumab use in a cohort of high-risk infants in Western Australia. Methods Using probabilistically linked administrative data, we conducted a birth cohort study within tertiary neonatal intensive care units (NICUs) born between 2002 and 2013. We described palivizumab use by patient characteristics, eligibility criteria according to guidelines over the period of study and identified predictors of its use. Results Of 24,329 infants admitted to tertiary NICUs, 271 (1.1%) were dispensed 744 palivizumab doses with 62.5% being dispensed to infants born 2010-2013. The median number of doses received was 2. A total of 2679 infants met at least one of three criteria for palivizumab (criteria 1: gestational age at birth < 28 weeks and chronic lung disease; criteria 2: gestational age < 28 weeks and Aboriginal; criteria 3: congenital heart disease not otherwise in criteria 1 or 2). The extent of palivizumab use differed across the 3 groups. Of 803 infants meeting criteria 1, 21.8% received at least 1 dose of palivizumab; 52.8% from 2010 onwards. From 174 infants meeting criteria 2, 14.4% received at least 1 dose; 43.1% from 2010 onwards and from 1804 births meeting criteria 3, only 3.7% received at least 1 dose; 5.4% from year of birth 2010 onwards). In adjusted analyses, being born after 2010, being extreme preterm, chronic lung disease, congenital lung disease and being born in autumn or winter were independent predictors of palivizumab use. Conclusion In this high-risk setting and notwithstanding the limitations of our data sources, the level of compliance of palivizumab use against current guidelines was low. Most doses were dispensed to infants meeting at least one high-risk criterion. Evidence of incomplete dosing is an important finding in light of recent developments of single dose monoclonal antibodies offering longer protection.